Technology and finance : challenges for financial markets, business strategies and policy makers - Balling, Morten; Lierman, Frank; Mullineux, A. W. (London ; New York : Routledge, 2003)
This volume represents the cutting edge of informed thinking on the implications of, and possible problems with, modern technology on contemporary finance.
Includes bibliographical references and index.
oif 21/08/15
Loan
Keywords: Banks and banking - technological innovations; Banks and banking; Financial institutions; Financial institutions - technological innovations; Financial services industry